2019
DOI: 10.1186/s12917-019-1782-3
|View full text |Cite
|
Sign up to set email alerts
|

Oral pre-administration of Purslane polysaccharides enhance immune responses to inactivated foot-and-mouth disease vaccine in mice

Abstract: BackgroundFoot-and-mouth disease (FMD) is one of the greatest disease threats to animal husbandry worldwide. Though various vaccines against foot-and-mouth disease virus (FMDV) have been developed, vaccine effectiveness is still not satisfactory. In this work, we studied the potential ability of Purslane polysaccharide (POL-P3b) as a nutrient food additive to enhance immune responses to FMD vaccination in mice.ResultsOur results demonstrated that oral administration of POL-P3b at mid- and high-doses significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Purslane extract (PE) has good antioxidant activity 20 because it contains polyphenols, small‐chain organic acids and saccharides. As a potential natural antioxidant, purslane has superior properties, including good stability, non‐toxicity and medicinal value, compared to synthetic antioxidants 21,22 . In addition, it is a popular in low‐calorie product and has health care efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Purslane extract (PE) has good antioxidant activity 20 because it contains polyphenols, small‐chain organic acids and saccharides. As a potential natural antioxidant, purslane has superior properties, including good stability, non‐toxicity and medicinal value, compared to synthetic antioxidants 21,22 . In addition, it is a popular in low‐calorie product and has health care efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous researches have showed that POL-P could increase the FMDV-speci c antibody production in mice immunized with FMD vaccines [10]. In the present study, the structural features of POL-P and the molecular mechanism were revealed in detail.…”
Section: Discussionmentioning
confidence: 61%
“…Portulaca oleracea L. polysaccharides (POL-P) have many pharmacological activities, such as antitumor, antioxidation and antiviral [7][8][9]. Our published paper have showed that POL-P could increase the IgG and isotypes antibody titers, promote SIgA secretion of intestinal mucosa in mice immunized with foot and mouth disease (FMD) vaccines [10]. However, the structural features and the mechanism of action are still unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Another study evaluated the potential of pre-administration of oral POL-P3b as an immunostimulator on foot-and-mouth disease vaccines. Similarly, the results suggested that dietary POL-P3b supplementation could enhance the immune response, including humoral and cellular responses [131].…”
Section: Immunomodulatory Effectsmentioning
confidence: 86%